Sex Differences in Case Fatality Rate of Patients With Severe Fever With Thrombocytopenia Syndrome - Zhao, Jing; Lu, Qing-Bin; Li, Hao; Yuan, Yang; Cui, Ning; Yuan, Chun; Zhang, Xiao-Ai; Yang, Zhen-Dong; Ruan, Shi-Man; Liu, Lan-Zheng; Du, Juan; Fang, Li-Qun; et al. (Frontiers in Microbiology, 2021)
Background: Severe fever with thrombocytopenia syndrome (SFTS) is a tick-borne disease with high mortality. However, detailed analysis is lacking to explore the complex effect of sex with age or comorbidities. Methods: A retrospective cohort study was performed among 2,938 SFTS patients entered during 2011–2020 in Xinyang, China. The case fatality rate (CFR) was estimated for their association with sex, age, and comorbidities by an interactive way. The difference of immune response between sex was explored in an age dependent way. Results: An overall CFR of 15.3% (450/2,938) was obtained, which appeared to be higher in males than in females [17.7% vs. 13.6%, adjusted odds ratio (aOR) = 1.24; 95% CI, 1.00–1.53; P = 0.048] and increased dramatically with age (P < 0.001). The associations between sex and SFTS fatal outcome were age-dependent and varied according to the status of comorbidities. The mortality-related risk conferred by older age was more pronounced in males, with aOR (95% CI) to be 5.76 (3.75–8.84) vs. 5.30 (3.54–7.95) in female. Sex-stratified analysis disclosed significant associations between death and comorbidities among female patients (aOR = 1.87, 95% CI: 1.40–2.49; P < 0.001), while none among males. Among females, the significant associations between presence of comorbidity and fatal outcome differed among age groups, with aOR (95% CI) decreased from 2.28 (1.16–4.46) in ≤60 years, to 2.06 (1.34–3.18) in 60–70 years and further to 1.55 (0.97–2.47) in >70 years. Altogether 194 SFTS patients were randomly selected for the test of B cells, natural killer (NK) cells, CD4 cells percentages, and anti-SFTSV IgM antibody level, the results revealed that males >60 years had significantly decreased percentages of B cells, CD4 cells, lower anti-SFTSV IgM antibody titer, and increased level of NK cells than male aged ≤60 years, while none of these age specific differences was observed in the females. This finding underlies the more pronounced age specific difference in CFR among male than female. Conclusions: Males had a significantly higher mortality of SFTS than did females, and more likely to be affected by aging for SFTS mortality. This difference can be explained by the effect from comorbidities and the host immunity. It is essential to take a sex- and age-based approach to SFTS treatment and management.